Effect of pepper (Capsicum sp) on productivity and egg quality of laying hens: a meta-analysis: https://doi.org/10.12982/VIS.2024.050 - Muhammad Fathin Hanif; Bambang Ariyadi; Muhlisin; Agus, Ali (Veterinary Integrative Sciences, 2024)
The restriction on the use of antibiotics as a growth promotant in poultry diets, due to their adverse effects, has led to increased use of feed additives with natural ingredients such as medicinal plants and herbs. Pepper (Capsicum sp) is a potential feed additive as an antibiotic alternative in laying hen diet. This meta-analysis aimed to determine the effect of pepper supplementation on the performance and egg quality attributes of laying hens. The PubMed, Scopus, Google Scholar, and Science Direct databases were searched for peer-reviewed randomized controlled trials written in English. Information on the moderators (hen age at the beginning of the intervention, pepper preparation form, inclusion level of pepper, and treatment duration) were required for inclusion in the meta-analysis, as well an acceptable explanation of randomization, statistical analysis of egg production and quality, and associated variance measurements, such as standard deviation or standard error. The meta-analysis included 19 research papers that met the criteria. Open meta-analyst for ecology and evolution (OpenMEE) software was used for all analyses. The pooled results demonstrated that supplementing with pepper reduced feed intake by −0.44 g/day, increased HDEP by 0.71% and egg yolk color by 5.7 but had no effect on FCR or egg weight compared to the control, after considering publication bias and heterogeneity. Hens provided diets with or without peppers had comparable HDEP. This meta-analysis indicates that pepper can be used as a feed additive in laying hens to increase egg production and egg yolk color